(untitled) (The Planet, 2023)
Background: Infertility is a global issue in reproductivehealth. Etiology Of infertility is multifactorial and fallopiantube abnormality being one of the most important causesaccounts for up to 40%of female infertility. saline infusionsonography (SIS) is gaining popularity and being widelypracticed and accepted as a screening tool in assessingtubal patency. Objectives: To compare the efficacy of tubalpatency test with saline infusion sonography andhysterosalpingography in infertile women. Methods andmaterial: It is a quasi-experimental study .120 consecutiveinfertile women in 25-40 years, who are ovulatingspontaneously or by ovulation induction who was neededtubal assessment included here. 60 patients went for salineinfusion sonography, 60 went for hysterosalphingographywhich was allocated by lottery. Result: Main outcome wasfind out the diagnostic accuracy of saline infusion sonography over conventionalhysterosalpingography for evaluation of tubal patency. tubal patency confirmed by SIS54(89.99%) had at least one tube patent. Tubal block 6(10.01%). HSG bilateral tubal patency40(66.67%), bilateral tubal block 15(25.00%), unilateral block 5(8.33%) .SIS had sensitivity86% specificity 97%,positive predictive value 97% and negative predictive value 83% in tubalpatency. Conclusion: SIS employed as a screening procedure to pick up subjects needing HSGand laparoscopy Low risk subjects for tubal factors in infertility, sonohysterosulphingographycan be. It is simple, relatively less expensive, minimally invasive procedure.